2017
DOI: 10.4467/24496138zps.17.003.6538
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between on-going terror attacks, military operations and wars and the well-being of Jewish and Arab three generations civilians in Israel

Abstract: Between the state of Israel independent declaration in 1948, until this very days, wars, military operations and on-going national terror had been its daily routine to cope with. Th e main goal of this study was to review published studies on the impact of those extreme negative life events on the well-being and mental health of various groups of Arab and Jewish civilians in Israel. In addition, this study emphasizes well-known PTSD risk factors related to terrorism, military operations and war in Israel, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Israel, a country of approximately 8 million people, has a long history of war and terrorist events. A systematic review of studies investigating the impact of war and terror on Israeli mental health concluded that increased physical and psychological exposure to war and terror is associated with increased symptoms, more so in women compared to men (Ron & Ron, ). Three Israeli nurses conducted two studies in this area.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Israel, a country of approximately 8 million people, has a long history of war and terrorist events. A systematic review of studies investigating the impact of war and terror on Israeli mental health concluded that increased physical and psychological exposure to war and terror is associated with increased symptoms, more so in women compared to men (Ron & Ron, ). Three Israeli nurses conducted two studies in this area.…”
Section: Review Of the Literaturementioning
confidence: 99%